2015
DOI: 10.2147/ott.s94300
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of SHOX2 DNA methylation in lung cancer: a meta-analysis

Abstract: The diagnostic value of SHOX2 DNA methylation in patients with lung cancer remains controversial. Thus, we performed a systematic review and meta-analysis to assess diagnostic accuracy of SHOX2 DNA methylation in the lymph node, bronchial aspirates, pleural effusion, plasma, and tumor tissue for lung cancer. We conducted a comprehensive literature search in PubMed, Ovid, the Cochrane library, and Web of Science databases in May 2015. The diagnostic sensitivity (SEN), specificity (SPE), positive likelihood rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, in recent decades, many researchers have found that SHOX2 also plays an important role in multiple cancers, including lung cancer ( Schneider et al, 2011 ; Hong et al, 2014 ; Sun et al, 2019 ). Interestingly, methylation detection of SHOX2 in sputum, blood, alveolar lavage fluid, and tissue of patients has been used to screen early lung cancer patients ( Zhao et al, 2015 ; Weiss et al, 2017 ; Zhang et al, 2017 ; Shi et al, 2020 ). It is worth noting that there is little research on the potential prognostic influence and molecular mechanism of SHOX2 in lung cancer, especially in non-small-cell lung cancer (NSCLC) [mainly lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC)].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent decades, many researchers have found that SHOX2 also plays an important role in multiple cancers, including lung cancer ( Schneider et al, 2011 ; Hong et al, 2014 ; Sun et al, 2019 ). Interestingly, methylation detection of SHOX2 in sputum, blood, alveolar lavage fluid, and tissue of patients has been used to screen early lung cancer patients ( Zhao et al, 2015 ; Weiss et al, 2017 ; Zhang et al, 2017 ; Shi et al, 2020 ). It is worth noting that there is little research on the potential prognostic influence and molecular mechanism of SHOX2 in lung cancer, especially in non-small-cell lung cancer (NSCLC) [mainly lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC)].…”
Section: Introductionmentioning
confidence: 99%
“…Among the six genes analyzed, SHOX2 exhibited the highest AUC and was the gene that better predicted malignancy among negative EBUS-TBNA samples. Methylated SHOX2 has been studied previously for detecting LC in lymph node samples obtained by EBUS-TBNA [24], in bronchial aspirates, pleural effusion, plasma, and tumor tissue [34]. A meta-analysis exploring SHOX2 methylation for LC diagnosis in different samples estimated a pooled sensitivity of 70% with 96% specificity (AUC = 0.96), supporting its value for confirming benignity for negative results [34].…”
Section: Discussionmentioning
confidence: 88%
“…CYP19A1 , a member of the cytochrome P450 family, was previously found to be highly expressed in GC and associated with an adverse prognosis; the silencing of its expression could be useful for GC treatment 31 , 32 . A previous study showed that SHOX2 methylation represent a potential biomarker for some cancers 33 37 . This gene was also shown to be related to unfavorable distant metastasis-free survival and could promote WASF3 transcriptional activity to induce the growth and metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%